2000
DOI: 10.1080/07373930008917780
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS OF SHRINKAGE PHENOMENON INBrachiaria brizanthaSEEDS

Abstract: ANALYSIS O F SHRINKAGE PHENOMENON IN Brachiaria briznntho SEEDS S. Arnosti ~r . ' , J.T. Reire', D.J.M. ~a r t o r i ' '~a c u l d a d ABSTRACTPicnometry and image analysis were used to measure and analyze the dimensional shrinkage of Brachiaria briza~rrlta seeds due to reduction in the moisture content. The data were statistically treated and an equation to relate the shrinkage phenomenon with the moisture content was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This treatment is considered necessary here since shrinkage is not symmetrical and non-uniform in most foods. Moreover, according to the bibliography (Arnosti et al 2000;Calli Pacco and Menegalli 2004;Leiva Díaz et al 2009;Mowla 2002, 2003;Moreira et al 2000;Ochoa et al 2002aOchoa et al , b, 2007Sjöholm and Gekas 1995;Raghavan and Venkatachalapathy 1999;Ratti 1994;Ratti and Crapiste 2008;Schultz et al 2007) most published shrinkage data are reported to be independent from drying operating conditions or, at most, dependent on air velocity or drying method (Martynenko 2008). On the contrary, evidence suggests that shape changes with velocity and drying method, notably drying rate (Panyawong and Devahastin 2007).…”
Section: Introductionmentioning
confidence: 88%
“…This treatment is considered necessary here since shrinkage is not symmetrical and non-uniform in most foods. Moreover, according to the bibliography (Arnosti et al 2000;Calli Pacco and Menegalli 2004;Leiva Díaz et al 2009;Mowla 2002, 2003;Moreira et al 2000;Ochoa et al 2002aOchoa et al , b, 2007Sjöholm and Gekas 1995;Raghavan and Venkatachalapathy 1999;Ratti 1994;Ratti and Crapiste 2008;Schultz et al 2007) most published shrinkage data are reported to be independent from drying operating conditions or, at most, dependent on air velocity or drying method (Martynenko 2008). On the contrary, evidence suggests that shape changes with velocity and drying method, notably drying rate (Panyawong and Devahastin 2007).…”
Section: Introductionmentioning
confidence: 88%
“…A linear dependence between apparent density and moisture content was reported by these authors in pears, carrots, potatoes, sweet potatoes and garlic. Arnosti, Freire, and Sartori (2000), working with Brachiaria prizanlha seeds, found that shrinkage coefficient depended on an adimensional moisture content (present moisture content/initial moisture content), while apparent density did not. Ramallo et al (2001) reported that shrinkage coefficient and apparent density of leaves of ''yerba mat e'' linearly depended on moisture content but were independent on drying temperature.…”
Section: Introductionmentioning
confidence: 96%
“…The model developed for individual particles, Equation (9), taking into account variations of the porosity during the drying process, is particularly interesting, as it can be extended to describe shrinkage behavior of packed beds. Although there are theoretical models providing physical interpretation for the shrinkage phenomenon, most researchers (Zielinska & Markowski, 2010;Ramos et al, 2010;Ochoa et al, 2007;Prado et al, 2006;Arnosti Jr. et al, 2000;Ratti, 1994;Lozano et al, 1983) have used empirical equations to represent the changes in volume and surface area as functions of moisture content. This is because empirical models allow the prediction of shrinkage without requiring the knowledge of physical properties, such as porosity which is not usually available.…”
Section: Experimental and Theoretical Approachesmentioning
confidence: 99%
“…This method can only be applied if the initial solid geometry was maintained during drying. When the shrinkage is accompanied by deformations, the use of volumetric displacement methods (buoyant forces) is recommended to determine the volume changes of material (Suzuki et al, 1976;Lozano et al, 1983;Ratti, 1994;Arnosti Jr. et al, 2000;Zielinska & Markowski, 2010;Ochoa et al, 2007). Volumetric displacement methods have been used by many researchers to determine the apparent volume of different solid materials.…”
Section: Experimental Measurementmentioning
confidence: 99%